Female Stereotypes in Cinderella’s Reconstructed Stories - Galang Yugo Primono; Sulasih Nurhayati (JSSH (Jurnal Sains Sosial dan Humaniora), 2022)
This study aims to find out female stereotypes depicted in the reconstructed stories of Cinderella in the children's storybook entitled Ketika Rapunzel Menjadi Rapinem (KRMP). These stories are mainly inspired by the classic fairy tale of Cinderella, which is then reconstructed through the archetype process. It is essential to study the stories due to the prevalent issue of female stereotypes. Women’s conditions in such reconstructed works certainly bring a perspective, especially the depiction of women, as existing social reflections. The study uses a qualitative descriptive method to support the goal. The data collection uses a purposive sampling technique by conducting in-depth readings on the reconstruction of Cinderella stories, representing women's stereotypes. The data is analysed using the feminism theory. As a result, the stories clearly and consistently define the stereotypes of women from their physical appearances, personality traits, domestic roles, and occupations. In this case, women's portrayal in the reconstructed versions openly continues to glorify physical beauty as a standard for women's appearance; on the other hand, they should also maintain femininity and do domestic works as housewives or caregivers.